CREATIVE TEACHING METHODS FOR STUDENTS OF NON-PHILOLOGICAL UNIVERSITIES (Academia Science Repository, 2023)
The command form of organization of activity is one of the effective forms of organization of managerial activity, which has become widespread in countries with developed democracies in many areas of human activity, including the field of education. This form is often referred to as a method, and the concept of “team approach” has been formed in management. This article analyzes the essence of creative team teaching in foreign language teaching.